San Pedro Community Center - Navarro, Nomer L. (Manila : National University, 2001)
As the Philippines continue to progress and facing the new Millennium, the Philippine government is striking for the search of the local development and industrialization of the country.
Preface -- Acknowledgement -- Dedication -- Chapter I. Introduction -- Chapter II. Methodology -- Chapter III. Terms of references -- Chapter IV. Design framework -- Chapter V. Analysis-- Chapter VI. Conclusion -- Bibliography -- Pictorial presentation of plates -- Appendices/Annexes -- Profile of proponent.
Includes bibliographical references.
Keywords: COMMUNITY CENTER